ID: 63. Issue 1 (November 2015) - Kalvakolanu, Dhan V.; Gade, Padmaja; Kimball, Amy; Dinardo, Angela C.
<x xml:space="preserve">Abstract</x> The molecular and genetic bases for the progression of chronic lymphocytic leukemia (CLL), an indolent disease, are poorly understood. The Death associated protein kinase 1 (DAPK1), an IFN-inducible calcium-calmodulin-dependent serine/threonine kinase, is a critical regulator of autophagy and apoptosis. Its expression is frequently suppressed in a wide variety of tumors including CLL. Recently, we have identified a novel non-STAT signaling pathway, where in an endoplasmic resident transcription factor ATF6, in association with the transcription factor C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> regulates the IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rcx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>-induced expression of DAPK1. IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rcx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives>-induced proteolytic processing of ATF6 and phosphorylation of C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> are obligatory for the formation of ATF6/C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> transcriptional complex that regulates DAPK1. Our studies show that in B-CLL, failure of IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rcx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> activated functional collaboration between C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> and/or ATF6 contributes to a loss of growth control via autophagy. We also show a correlation between loss of DAPK1 levels and a failure of ATF6 and/or C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> activation primary CLL tumors. Restoration of ATF6 or C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> into respective defective-primary tumor cells, re-established DAPK1 expression. Furthermore, IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7rcx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ</alternatives> and chemotherapeutics failed to activate autophagy in CLL patient samples lacking ATF6 or C/EBP-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qpc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives>.Together, these results identify a mechanistic basis for the loss of DAPK1 expression, drug resistance and progression of CLL.